PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR IPAS KELAS IV SD NEGERI JELEGONG 02 - Aulia, Siti Rahma Suci; Indriani, Rina; Hamdani, Acep Roni (Cahaya Ilmu Bangsa Institute, 2025)
This study was motivated by the low learning outcomes of fourth-grade students at SDN Jelegong 02. The research aimed to (1) describe the learning process using the Problem Based Learning (PBL) model assisted by instructional videos, (2) determine the effect of the PBL model assisted by instructional videos on improving students’ science learning outcomes, and (3) measure the increase in students’ learning outcomes through the implementation of the model. The study employed a quasi-experimental method with a nonequivalent control group design. The sample consisted of two classes: class IVA as the experimental group and class IVB as the control group. Data were collected through tests, observations, and documentation, and analyzed using normality and homogeneity tests. The results showed that the implementation of the PBL model assisted by instructional videos was effective and enhanced student learning activities. The experimental class’s average score increased from 43.02 (pretest) to 80.04 (posttest), while the control class increased from 36.00 to 64.00. The effect size value of 1.131 indicates a large effect, meaning that the PBL model assisted by instructional videos had a significant impact on improving students’ learning outcomes. Keywords: Problem Based Learning, Instructional Video, Learning Outcomes, Elementary School Abstract Penelitian ini dilatarbelakangi oleh rendahnya hasil belajar siswa kelas IV SDN Jelegong 02. Tujuan penelitian adalah untuk mengetahui proses pembelajaran, pengaruh, dan peningkatan hasil belajar menggunakan model Problem Based Learning (PBL) berbantuan video pembelajaran pada mata pelajaran IPAS. Metode yang digunakan yaitu quasi eksperimen dengan desain nonequivalent control group design. Sampel penelitian terdiri dari kelas IVA sebagai kelas eksperimen dan IVB sebagai kelas kontrol. Data dikumpulkan melalui tes, observasi, dan dokumentasi, kemudian dianalisis dengan uji normalitas dan homogenitas. Hasil penelitian menunjukkan bahwa penerapan model PBL berbantuan video pembelajaran berjalan efektif dan meningkatkan aktivitas belajar siswa. Rata-rata nilai pretest dan posttest kelas eksperimen meningkat dari 43,02 menjadi 80,04, sedangkan kelas kontrol dari 36,00 menjadi 64,00. Nilai effect size sebesar 1,131 termasuk kategori tinggi, yang berarti model PBL berbantuan video pembelajaran berpengaruh signifikan terhadap peningkatan hasil belajar siswa. Kata Kunci: Problem Based Learning, Video Pembelajaran, Hasil Belajar, Sekolah Dasar